Fragmented monopole crystal, dimer entropy, and Coulomb interactions in Dy2Ir2O 7 - Cathelin, V. (2020)
Neutron scattering, specific-heat, and magnetization measurements on both powders and single crystals reveal that Dy2Ir2O7 realizes the fragmented monopole crystal state in which antiferromagnetic order and a Coulomb phase spin liquid coinhabit. The measured residual entropy is that of a hard-core dimer liquid, as predicted. Inclusion of Coulomb interactions allows for a quantitative description of both the thermodynamic data and the magnetization dynamics, with the energy scale given by deconfined defects in the emergent ionic crystal. Our data reveal low-energy excitations, as well as a large distribution of energy barriers down to low temperatures, while the magnetic response to an applied field suggests that domain wall pinning is important, results that call for further theoretical modeling.